TRADITIONAL MEDICINAL KNOWLEDGE OF INDIGENOUS PEOPLE AND ACCESS AND BENEFIT SHARING: A STUDY IN LEGAL PERSPECTIVES - Bajpai, Shreya; Sikarwar, Chaya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India takes pride in being the custodian of invaluable traditional medical knowledge derived from its rich natural resources. This knowledge has its roots in the continuous embrace and interaction with biodiversity. As a highly diverse nation, India has a select group of individuals dedicated to preserving the biodiversity, thereby safeguarding their traditional medicinal wisdom. These indigenous people or tribes have invaluable traditional knowledge of certain skills and medicines. The transmission of this information to the general population becomes difficult since these indigenous or tribal people are constrained by territorial boundaries. However, invading their country is not a problem in order to financially exploit the indigenous people’s TMD knowledge base. This has led to both the eradication of their biodiversity and the denial of it. The biodiversity legislation and Indigenous People Law were designed to protect biodiversity and the rights of indigenous group of people as a result of this expanded use of traditional medicinal knowledge.Native Indians who live in tribal areas in India use traditional medical knowledge to maintain their health and, in turn, their way of life. Multinational corporations frequently bio-pirate this tribal group’s traditional medical knowledge in order to sell it as a medicine. The primary legal issue that arises in this situation is the denial of the right to access benefit sharing, which is the significant legal paradigm introduced by national legislation adopted in accordance with the aforementioned universal laws. In addition to the Universal Laws safeguarding the rights of Indigenous groups, the Nagoya Protocol of 2010 and the Bonn Guidelines of 2001 regulate access and benefit-sharing on a global scale. Within India, the Access and Benefit Sharing Mechanism is governed by the Biodiversity Act of 2002, the Biological Diversity Rules of 2004, and the Access and Benefit Sharing Guidelines of 2014. These legislative measures aim to ensure the equitable and fair distribution of benefits by the state. Concurrently, sections 3 and 7 of the Biological Diversity Act, 2002, provide unrestricted access to biological diversity for any Indian citizen, as well as any corporate entity, association, or organization registered in India. The law stipulates that the State Biodiversity Board must be notified in advance to obtain such biological diversity knowledge. This paper examines the legality of pharmaceutical companies’ persistent bioprospecting activities in relation to the rights affirmed for Indigenous groups. Additionally, it investigates whether the Biological Diversity Act of 2002 infringes upon the access and benefit-sharing rights of Indigenous or Tribal groups.